MENINGKATKAN HASIL BELAJAR GEOGRAFI MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE TGT - Muh Khamid (Prodi Pendidikan IPS, Universitas Tanjungpura, 2021)
The problem in this classroom action research is that the learning outcomes of students in class XI IPS 3 at SMAN 3 Simpang Hilir are low. The purpose of the study was to determine the process of each cycle in improving the learning outcomes of geography on population dynamics in Indonesia for development planning using the TGT type cooperative learning model for students in class XI IPS 3 at SMAN 3 Simpang Hilir and to find out whether there was an increase in learning outcomes of geography on population dynamics in Indonesia for development planning uses the TGT type cooperative learning model for students in class XI IPS 3 at SMAN 3 Simpang Hilir. This type of research is classroom action research which is carried out in class XI IPS 3 at SMAN 3 Simpang Hilir. This action research procedure includes four stages, namely planning, implementation, observation and reflection. Data collection techniques by observation, post test, report. Data analysis technique using descriptive. Overall, the level of teacher mastery from cycle 1 to cycle 2 increased from 83, 87% (good) to 97,41% (very good). There is an increase in the average learning outcomes from cycle 1 to cycle 2 of 12.83 so it can be concluded that learning uses the Team Games Tournament (TGT) cooperative learning model on population dynamics material in Indonesia for development planning in class XI IPS 3 SMA N 3 Downstream intersection can improve student learning outcomes.Keywords: improve, geography learning outcomes, TGT.